Optimization of Gobak Sodor Based Neuroscience Learning Game as Character Education in Intellectual Disabilities - Ida Ayu Dian Pramantik (JUMORA: Jurnal Moderasi Olahraga, 2021)
The purpose of writing this article is to find out the optimization of traditional gobak sodor neuroscience learning-based game activities as character education in intellectual disability with grade medium (ATG). Referring to the problems, most schools do not have policies and administrations regarding character education, most schools that have an environment that supports the implementation of character education, most teachers do not have good knowledge and attitude in character education, most teachers do not have good competence, most schools have used the curriculum and most teachers have not used assessments that are suitable for children.  Character education and most of the community has not supported the course of character education. The purpose of writing this article is to find out the optimization of traditional "gobak sodor" neuroscience learning-based game activities as character education in children ATG. The method used in writing this article is the study of non-systematic literature from national & international database. Based on the concept of a previous relevant frame of mind, schema, and research, it can be concluded that there will be optimization of traditional "gobak sodor" game activities based on neuroscience learning as character education in children. Optimization of adaptive physical education learning can occur through synergistic contributions through neuroscience learning in traditional games and character education of lightly impaired children. The results of adaptation of these mechanisms are able to reduce the barriers of cognitive domains, practice domains, and social domains of lightly impaired children. Keywords: character, neuroscience learning, traditional games, ATG